Stereotyping the grammatical term in the approaches verbs towards an integrative vision in structure and semantics - Mahassneh, ALI (Al-Adab Journal, 2025)
There is an interest in the Arab heritage of linguists and grammarians terminology, it has accompanied them from the beginning of linguistic and grammatical authorship, and the terms have a specific significance to the extent of saying: (There is no Moshaha (confusion) in the term) in terms that the words have a recognized terminological Indication, as long as they agree on the one hand and commonly used on the other. However, what was decided that (there is no confusion in the term) needs careful Meditation and deep reflection, it may be agreed upon and it received from the commonness of what he received, but it is problematic in several ways, such as the term has two general and private Indications, as we find in the Indication of the term (Approaches verbs) which is general and the verbs of hope and Initiation verbs private on ) Kada  Awshaka and Karaba)  . There is a plurality of terminology as we find in the initiation verbs or the term does not reveal what it is in terms which it must be inclusive. It is noted that the plural and prohibition limits covered by the term in the section of Approaches verbs.    This research deals with the study of the issue of the grammatical term in the section of the approaches verbs, and shows that the term had disorders in semantics. We find abundant terms in this section in that grammarians were not together in their release and in their use. It seeks to put the grammatical term in the approaches verbs to the test in order to reach the mechanism of its development and standardization.